Procedural group identification - Dinko Dimitrov; Shao Chin Sung; Yongsheng Xu (Bielefeld University, Institute of Mathematical Economics (IMW), 2006)
In this paper we axiomatically characterize two recursive procedures for defining a social group. The first procedure starts with the set of all individuals who are defined by everyone in the society as group members, while the starting point of the second procedure is the set of all individuals who define themselves as members of the social group. Both procedures expand these initial sets by adding individuals who are considered to be appropriate group members by someone in the corresponding initial set, and continue inductively until there is no possibility of expansion any more.
urn:nbn:de:hbz:361-9805
Keywords: D63; D71; 330; Consensus; Liberalism; Procedure; Social identity; Public Choice; Soziale Gruppe; Theorie